MAINTAIN OF RED TILAPIA (Oreochromis sp.) USED OF PEAT SWAMP WATER IN BIOFLOCS TECHNOLOGY - Mifta huljannah Hsb; Iskandar Putra; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted for 50 days from August to September 2017. At Laboratory of Aquaculture Technology, Marine and Fisheries Faculty, University of Riau. The aim of this research was to know the effect of artificial feeding with a different percentage of the growth and survival rateof Red Tilapia by using biofloc system on peat swamp water.This research was using experimental method by completely random design (RAL) one factor with three replication. The fish used in this research with size 5 - 7 cm.The result showed that feeding with a different percentage of growth and survival rate of Red Tilapia by using bifloc on peat swamp water. In addition, it also affected the absolute weight growth, absolute length growth, feed efficiency and feed conversion ratio. The optimal dose was at FR 5% by giving the absolute weight growth was 4.46 g, absolute length was 4.48 cm, feed efficiency was 88.46%, feed conversion ratio was 1.12, and survival rate was 95.83%. Key word : Red tilapia,Biofloc, Growth, Feeding rate, Peat swamp water